القدرة الكامنة للتريتيكالي (x.Triticosecal Wittmack) في نظام الزراعة المختلطة مع البقوليات العلفية في المناطق البعلية (استقرار ثانية وثالثة) من سوريا - رقية, نزيه; كيال, حامد; لاربي, أساموا; حبيب, نبيل (Latakia University Journal -Biological Sciences Series, 2019)
Two experiments designed in a randomized complete block were conducted to investigate the potential of triticale as the sole forage crop and in mixtures at two sites in north-west of Syria’s Mediterranean environment, using triticale (x.Triticosecale Wittmack), barley (Hordum sativum L.), common vetch (Vicia sativa L.) and grasspea (Lathyrus sativus L.) monoculture as well as in mixtures in one seeding ratio (1:1), during 2006/2007. Data of fresh and dry matter, legumes contribution in mixtures, relative yield total (RYT) and competitive ratio (CR) showed that the booting stage is the optimum harvesting date for triticale as a sole crop or in mixture. RYT values exceeded unity in cut 2 in the two sites, whereas the contrary was observed at cut1. Legume proportions were better in triticale mixtures in both sites and cutting dates. CR values indicated that triticale is less competitive in mixtures than barley. Cereals were more competitive than legumes. نُفذ البحث في موقعين شمال غرب سوريا: تل حديا (استقرار ثانية)، وبريدة (استقرار ثالثة)، وفق تصميم القطاعات العشوائية الكاملة باستخدام محصولين نجيليين: تريتيكالي (x.Triticosecale Wittmack) وشعير (Hordum sativum L.)، ومحصولين بقوليين: بيقية (Vicia sativa L.) وجلبان (Lathyrus sativus L.) بمعدل بذر 1:1 في الزراعة المختلطة، خلال الموسم الزراعي 2006/2007، لدراسة إنتاجية المادة الخضراء والجافة، والنسبة المئوية للبقوليات في معاملات الخلط مع النجيليات، وإجمالي الغلة النسبية RYT ومعامل التنافس في موعدي الحش، حيث تبين أن الموعد الأمثل لحش التريتيكالي كمحصول منفرد أو مختلط مع البقوليات هو مرحلة الحبل. تجاوزت قيم RYT في موقعي التجربة الواحد الصحيح في موعد الحش الثاني، في حين لوحظ العكس في الموعد الأول، وكانت النسبة المئوية للبقوليات في معاملات خلط التريتيكالي متفوقة معنوياً على معاملات خلط الشعير في كل من موقعي التجربة وموعدي الحش. كان التريتيكالي أقل منافسةً من الشعير لدى خلطه مع البقوليات. وعموماً كانت النجيليات أكثر منافسةً من البقوليات في الزراعة المختلطة.